Embedded system design for home security - Neo, Jason Jun Wei (2013)
Home security is a globally concerned issue. Recently, with the rapid advancement in Information Technology and Wireless Communication technologies, more Home Security systems are developed. People use them as fire alarm, burglar alarm and video surveillance systems.